Cumulative incidence of restenosis in the endovascular treatment of extracranial carotid artery stenosis: a meta-analysis. (31st January 2019) - Clavel, Pierre; Hebert, Solène; Saleme, Suzana; Mounayer, Charbel; Rouchaud, Aymeric; Marin, Benoit
Abstract : Objective: To assess the cumulative incidence of restenosis and stroke after stenting for cervical carotid artery stenosis. Methods: We reviewed PubMed, ScienceDirect, and Scopus and included all studies reporting restenosis after stenting. The cumulative incidence of restenosis at 6 and 12 months was calculated. We also estimated the cumulative incidence of ipsilateral stroke within 30 days after stenting. Random effect meta-analysis and meta-regression were performed using relevant study level covariates. Sources of heterogeneity were investigated. Results: Among 7765 records, 40 studies were selected. 15 943 patients and 16 337 carotid arteries were considered. The overall pooled cumulative incidence of restenosis >50% at 12 months was 5.7% (95% CI 3.8% to 8.6%), >70% at 12 months was 5.2% (95% CI 3.3% to 8.2%), >50% at 6 months was 3.9% (95% CI 2.2% to 6.8%), and ipsilateral stroke within 30 days after stenting was 1.6% (95% CI 1.0% to 2.5%) without association with the use of an embolic protection device. We did not identify any relevant source of heterogeneity of the cumulative incidence of restenosis >50% at 12 months. Mean age explained 80.9% (R 2 =80.9%, p=0.01) of heterogeneities of restenosis >70% at 12 months. The presence of hostile neck explained 53.9% (R 2 =53.9%, p=0.03) of heterogeneities of restenosis >50% at 6 months. Conclusion: This meta-analysis showed a low cumulative rate of restenosis at 12 months and ipsilateral stroke within 30 days after stenting. Older patients and those with hostile neck present a lower risk of in-stent restenosis. The use of an embolic protection device was not associated with a lower risk of stroke.